Effect of electron irradiation and heat on the structure of hairtail surimi. (September 2015) - Lin, Xianping; Yang, Wenge; Xu, Dalun; Wang, Lili
Abstract: Hairtail surimi was treated with electron radiation and heat, the chemical interactions, thermal properties and the structural changes were determined. The chemical interaction data indicate that the contribution of disulfide bonds to heat-induced gel formation was decisive. Irradiation promoted the formation of disulfide bonds during the cooking. Differential scanning calorimetry showed that the myosin and actin thermal transitions of irradiated surimi shifted to lower temperatures. And the myosin thermal stability of irradiated surimi was lower than unirradiated surimi. The Fourier transform infrared and Raman results showed the irradiation and heat treatments decreased the α-helix structure content and increased β-sheet structure content. This study may provide useful information for the effect of irradiation on the surimi gel properties. Highlights: The effects of irradiation and heat on surimi structure were investigated. Disulfide bonds were the main chemical interaction of heat-induced gel. The myosin thermal stability of irradiated surimi was lower than unirradiated surimi. The decrease in α-helix structure and increase in β-sheet structure were observed.